EFFECTIVE STRATEGIES TO IMPROVE ENGLISH READING COMPREHENSION - Seventri, Seventri; Septia Napa; Kurnia Febianti (PT. Intelek Cendikiawan Nusantara, 2024)
The importance of improving reading skills by utilizing various strategies such as strategic reading, critical thinking, active reading, and receiving feedback. These techniques help individuals in better understanding the main ideas, analyzing information, and asking relevant questions in texts, ultimately leading to improved comprehension. This is essential not only for writing effectively but also for enhancing the overall reading process by enabling individuals to read faster and more efficiently. Moreover, enhancing reading skills can have a significant impact on academic and professional success by improving performance on English proficiency tests like IELTS and TOEFL. The ability to think critically and communicate effectively is also highlighted as a direct benefit of improving reading skills. Additionally, the paragraph mentions how an enhanced reading ability can lead to a more enjoyable experience in entertainment reading, as well as a better understanding of various types of texts, ultimately increasing knowledge and promoting better discussion and critical thinking skills. In conclusion, the paragraph underscores the multifaceted benefits of improving reading skills, ranging from enhancing communication and cognitive abilities to achieving better academic and professional performance. By emphasizing the importance of strategies like critical thinking, active reading, and receiving feedback, individuals can experience a significant improvement in their comprehension abilities, leading to better writing, faster reading, and more effective communication. Ultimately, the paragraph underscores how enhancing reading skills can have a profound impact on various aspects of an individual’s personal and professional life